Medication discrepancies among hospitalized patients with hypertension: assessment of prevalence and risk factors - Rana Abu Farha; Alaa Yousef; Lobna Gharaibeh; Waed Alkhalaileh; Tareq Mukattash; Eman Alefishat (BMC, 2021)
Abstract Background Medication errors remained among the top 10 leading causes of death worldwide. Furthermore, a high percentage of medication errors are classified as medication discrepancies. This study aimed to identify and quantify the different types of unintentional medication discrepancies among hospitalized hypertensive patients; it also explored the predictors of unintentional medication discrepancies among this cohort of patients. Methods This was a prospective observational study undertaken in a large teaching hospital. A convenience sample of adult patients, taking ≥4 regular medications, with a prior history of treated hypertension admitted to a medical or surgical ward were recruited. The best possible medication histories were obtained by hospital pharmacists using at least two information sources. These histories were compared to the admission medication orders to identify any possible unintentional discrepancies. These discrepancies were classified based on their severity. Finally, the different predictors affecting unintentional discrepancies occurrence were recognized. Results A high rate of unintentional medication discrepancies has been found, with approximately 46.7% of the patients had at least one unintentional discrepancy. Regression analysis showed that for every one year of increased age, the number of unintentional discrepancies per patient increased by 0.172 (P = 0.007), and for every additional medication taken prior to hospital admission, the number of discrepancies increased by 0.258 (P= 0.003). While for every additional medication at hospital admission, the number of discrepancies decreased by 0.288 (P < 0.001). Cardiovascular medications, such as diuretics and beta-blockers, were associated with the highest rates of unintentional discrepancies in our study. Medication omission was the most common type of the identified discrepancies, with approximately 46.1% of the identified discrepancies were related to omission. Regarding the clinical significance of the identified discrepancies, around two-third of them were of moderate to high significance (n= 124, 64.2%), which had the potential to cause moderate or severe worsening of the patient´s medical condition. Conclusions Unintentional medication discrepancies are highly prevalent among hypertensive patients. Medication omission was the most commonly encountered discrepancy type. Health institutions should implement appropriate and effective tools and strategies to reduce these medication discrepancies and enhance patient safety at different care transitions. Further studies are needed to assess whether such discrepancies might affect blood pressure control in hypertensive patients.